The DHET's approach to establishing a credible mechanism for skills planning in South Africa - Alphonsus, Naomi Sumangala (My University, 2016)
Skills in South Africa are seen as essential for building the economy. This is why the Department of Higher Education and Training (DHET) sees developing a skills planning mechanism as important in the current context. The 2013 White Paper on the Post-School Education and Training System says that the function of skills planning should be centralized in DHET, with support from universities and/or other national research institutes. More specifically, DHET (2013) suggests that skills planning is required in the short, medium, and long term in order to shape the education system accordingly to meet the demand for skills. The literature on skills planning is full of debates on the kinds of skills planning that are possible in different contexts of economic and education systems. There are different notions of what skills planning is, how possible it is to predict skills demand, and how this should be done. There are also differences in ways in which economies are managed which have direct implications for skills planning. However imperfect, skills planning is needed as it provides an indication of what skills are needed to enable development in the country and provide guidance for the state to support initiatives. This study investigates the emerging skills planning mechanism in South Africa, the views of different stakeholders in this process and the projects that form part of skills planning. It argues that in the South African environment, skills planning has focused on the elements potentially needed to plan skills, however it is unclear how these elements will work together in a skills planning mechanism
Thesis (Master of Education), University of the Witwatersrand, Faculty of Humanities, School of Education, 2016
Keywords: Education and state--South Africa; Economic development--Effect of education on--South Africa; Skilled labor--Government policy--South Africa; Vocational education--South Africa